Pemanfaatan Teknologi Artificial Intelligence Pada Manajemen Strategi Perusahaan (Fakultas Ekonomi Universitas Tjut Nyak Dhien Medan, 2024)
This study aims to examine the integration of Artificial Intelligence (AI) in strategic management, focusing on market analysis, predictive analytics, and operational efficiency. The research employs a qualitative method with a case study approach on leading companies that have successfully implemented AI. The findings reveal that AI adoption significantly enhances organizational adaptability, competitive advantage, and innovation capacity. Furthermore, AI efficiently analyzes large datasets, supports real-time data-driven decision-making, optimizes operational efficiency by up to 30%, and accelerates product and service innovation, boosting customer satisfaction. However, key challenges include organizational resistance to change and data privacy issues. This study concludes that strategic AI implementation offers substantial benefits to companies, provided ethical and technical barriers are addressed prudently.